The Role of Organizational Commitment Mediation in the Relationship Between Human Resource Management Practices and Employee Engagement Towards Employee Performance - Suharno Pawirosumarto; Syafira Yusmeiliani; Fifi Alayda Sari (International Journal of Artificial Intelligence Research, 2022)
This study aims to examine and explain the effect of the relationship between human resource management practices and employee engagement on employee performance through organizational commitment as a mediator variable. The approach used in this study uses quantitative research methods. The sampling technique used a random sample with a total of population 143 employees. Active data in this study was analyzed using Partial Least Square (PLS) with SmartPLS 3.0 software on a computer. The results in this study reveal a significant positive relationship between human resource management practices and employee engagement through organizational commitment on employee performance. Implications for this study was to obtain empirical evidence about the factors that influence employee performance, such as human resource management/HRM practices, employee engagement and organizational commitment. So that the IT Division Project Click Indomaret can improve and improve organizational commitment to get higher employee performance and impact on the company to achieve its goals.